2020
DOI: 10.5336/jcog.2020-74215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between the Level of Vitamin D in Maternal Blood and Breast Milk and Postpartum Depression

Abstract: This study aimed to evaluate the relationship between postpartum depression (PPD) and vitamin D levels in maternal blood and breast milk. Material and Methods: The study included women who presented to a polyclinic between December 2017 and August 2018, 4-6 weeks after having given live birth, who were aged between 18 and 40 years and married, gave birth after a planned single pregnancy, were feeding their baby with only breast milk and stated that they were taking vitamin D supplementation at the dose recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One study utilized a HPLC method and reported the unlikely situation where the 2(OH)D 3 concentration was 30 nmol/L higher in HM than in serum in both vitamin D-supplemented and unsupplemented mothers ( 63 ). The second study used an automated chemiluminescence analyzer validated for serum but not for HM and described high analytical limits (18 nmol/L) ( 64 , 65 ). These assays may have suffered from inadequate specificity and cross-reactivity leading to spurious elevated concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…One study utilized a HPLC method and reported the unlikely situation where the 2(OH)D 3 concentration was 30 nmol/L higher in HM than in serum in both vitamin D-supplemented and unsupplemented mothers ( 63 ). The second study used an automated chemiluminescence analyzer validated for serum but not for HM and described high analytical limits (18 nmol/L) ( 64 , 65 ). These assays may have suffered from inadequate specificity and cross-reactivity leading to spurious elevated concentrations.…”
Section: Discussionmentioning
confidence: 99%